Soil microbiome transplantation to enhance the drought response of Salvia officinalis L. - Abou Jaoudé, Renée; Luziatelli, Francesca; Ficca, Anna Grazia; Ruzzi, Maurizio (Frontiers in Microbiology, 2025)
IntroductionSoil microbiome transplantation is a promising technique for enhancing plant holobiont response to abiotic and biotic stresses. However, the rapid assessment of microbiome-plant functional integration in short-term experiments remains a challenge.MethodsThis study investigates the potential of three evergreen sclerophyll species, Pistacia lentiscus (PL), Rosmarinus officinalis (RO), and Juniperus phoenicea (JP), to serve as a reservoir for microbial communities able to confer enhanced tolerance to drought in Salvia officinalis cultivated under water shortage, by analyzing biomass production, plant phenotype, plant ecophysiological responses, and leaf metabolome.ResultsOur results showed that the inoculation with the three rhizomicrobiomes did not enhance total plant biomass, while it significantly influenced plant architecture, ecophysiology, and metabolic responses. The inoculation with the JP rhizomicrobiome led to a significant increase in root biomass, resulting in smaller leaves and a higher leaf number. These morphological changes suggest improved water acquisition and thermoregulation strategies. Furthermore, distinct stomatal conductance patterns were observed in plants inoculated with microbiomes from PJ and PL, indicating altered responses to drought stress. The metabolome analysis demonstrated that rhizomicrobiome transplantation significantly influenced the leaf metabolome of S. officinalis. All three rhizomicrobiomes promoted the accumulation of phenolic compounds, terpenoids, and alkaloids, known to play crucial roles in plant defense and stress response. Five molecules (genkwanin, beta-ionone, sumatrol, beta-peltatin-A-methyl ester, and cinnamoyl-beta-D-glucoside) were commonly accumulated in leaves of inoculated sage, independently of the microbiome. Furthermore, unique metabolic alterations were observed depending on the specific inoculated rhizomicrobiome, highlighting the specialized nature of plant-microbe interactions and the possible use of these specific molecules as biomarkers to monitor the recruitment of beneficial microorganisms.DiscussionThis study provides compelling evidence that microbiome transplantation can induce phenotypic and metabolic changes in recipient plants, potentially enhancing their resilience to water scarcity. Our findings emphasize the importance of considering multiple factors, including biomass, physiology, and metabolomics, when evaluating the effectiveness of microbiome engineering for improving plant stress tolerance.